Fatigue load model of orthotropic steel deck for port highway in China - Peng, Xi; Wang, Kunpeng; Yang, Qiuwei; Xu, Bin; Di, Jin (Frontiers in Materials, 2023)
Vehicle load is an important factor for the fatigue damage of the orthotropic steel decks. The traffic vehicles for port highway in China are mainly multi-axle container trucks, which show different characteristics from conventional highways. Based on the multi-period traffic flow data collected by weight-in-motion system of a bridge over the sea in Zhejiang, China, this study has investigated the traffic load characteristics of the port highway bridge. Eight typical vehicles of fatigue load spectrum are classified according to the number of axles and wheelbase. The distribution characteristics of the gross vehicle weight (GVW) and axle weights of typical vehicles are analyzed by lane. Depended on the equivalent fatigue damage principle, the vehicle load spectrum for fatigue evaluation of the port highway bridges is established. The results show that the average proportion of the trucks (weighing greater than 3 tons) in the total traffic flow is 73.2%, and trucks with more than four-axle accounted for 89.0%. Heavy vehicles are mainly concentrated on the outer lanes, and the probability of vehicles driving in the heavy lane increases with the increase of GVW. The maximum equivalent GVW is 62.5 tons, which appeared in V7 in the exiting island direction. The simplified fatigue vehicle model in the heavy lane for Chinese port highway bridges is proposed, based on the six-axle vehicle which contributed the most fatigue damage. The proposed fatigue load model can better represent the actual traffic load level of port highway bridges in China.